Therapeutic effects of Bajakah kalalawit extract (Uncaria gambir Roxb.) in HCl/ethanol-induced rats as an animal model in acute gastritis: UHPLC MS/MS profiling and in vivo approach with in silico validation - Aulia Andi Mustika, Lina Noviyanti Sutardi, Andriyanto Andriyanto, Sharon Aurellia, Anisa Rahma, Rahayu Woro Wiranti, Andhika Yudha Prawira, Derajat Taruno Jati, Ekowati Handharyani, Setyanto Tri Wahyudi, (Journal of Applied Pharmaceutical Science, 2025)
Uncaria gambir Roxb., a plant known for its health-promoting properties and rich in bioactive compounds, offers an alternative treatment for acute gastritis. This research involved the approach of network pharmacology, pathway analysis, and molecular docking to predict signaling pathways of Bajakah kalalawit (Uncaria gambir Roxb.) extract in treating acute gastritis. The results were validated through an in vivo experiment using 25 rats, divided into normal healthy group, negative control, positive control, and treatment groups, and administered with the extract at a dose of 100 and 200 mg/kg BW. The rats were induced with acute gastritis using HCl/ethanol. In vivo parameters include the severity of gastric lesions, histopathological examination, ELISA assay, and immunohistochemistry to measure the levels of pro-inflammatory cytokines, including interleukin (IL)-6 and tumor necrosis factor (TNF)-α. Network pharmacology proved that there was a significant connection between the active secondary metabolite of the extract and acute gastritis-related genes. Although molecular docking proved that these compounds have limited potential in directly inhibiting TNF-α and IL-6, the in vivo findings nonetheless proved the gastroprotective effect, where the administered groups showed reduced gastric lesions and retained mucosal integrity through histopathological staining. The results of immunohistochemistry and ELISA proved that the extract modulated the levels of TNF-α and IL-6.
Keywords: Acute gastritis, active compounds, Bajakah kalalawit, Uncaria gambir